Systematic Literature Review for Lightweight Authentication Algorithm in the IOT - Sakiinah Altaf Hussain; Azni Haslizan Ab Halim; Najwa Hayaati Mohd Alwi (Penerbit UMT, 2024)
Indexed by Scopus/ERA/MyCite